The Future of Financial Market- Is the World Without Money Possible - Krzysztof MARECKI; Zbigniew GRZYMAŁA; Agnieszka WOJCIK-CZERNIAWSKA (Communications of International Proceedings, 2022)
Money is an enormous force, regardless of how you look at it. Even though people utilize money daily, the origin and operation of money appear to be cloaked in folklore and historical secrets. Money is an important part of today's economy, although we seldom see a meaningful, open dialog about what money is and what significant role for society's evolution. There are some things most people never survive without this life. Consider the potentially catastrophic consequences of stripping people of those through everything that humanity would not be whole without. Consider a world without money as a distinct medium of exchange, a key regulator of an economy, and a substitute for products and services. Seeking to picture a future without money is akin to imagining the sun not shining. It's hard or even impossible to consider as money is such an important factor in our life. Without a doubt, a life without money will ameliorate, if not entirely eradicate, all of these issues.
Keywords: Money; Currency; World; Life; Cash